The screening of the safety profile of polymeric based amoxicillin nanoparticles in various test systems. (15th September 2021) - Guncum, Enes; Bakirel, Tulay; Anlas, Ceren; Isiklan, Nuran; Ustun Alkan, Fulya; Charehsaz, Mohammad; Aydin, Ahmet
Graphical abstract: Highlights: The safety profile of amoxicillin nanoparticles (AmxNPs) were evaluated in both in vivo and in vitro test systems. AmxNPs have no genotoxic effect in bacterial and mammalian cells. AmxNps did not cause a significant change in biochemical parameters in broilers. These results illustrate that AmxNPs may be a promising drug for future therapeutic usage. Abstract: Nanotechnology-based drugs show superiority over conventional medicines because of increased bioavailability, lower accumulation in non-target tissues, and improved therapeutic index with increased accumulation at target sites. However, it is important to be aware of possible problems related to the toxicity of these products, which have therapeutically superior properties. Accordingly, the present study was designed to investigate the safety profile of amoxicillin nanoparticles (AmxNPs) that we developed to increase the oral bioavailability of amoxicillin (Amx) in poultry. In the first part of the study, the genotoxicity potential of AmxNPs was evaluated using the Ames test and the in vitro comet assay. The results of Ames test showed that none of the tested concentrations of Amx and AmxNPs cause a significant increase in the revertant number of Salmonella typhimurium strains TA98, and TA100, either with or without metabolic activation. Similarly, the comet assay revealed that AmxNPs did not induce DNA damage at any of the concentrations used, whereas high-dose (200 μg/mL) of Amx caused a significant increase in the percentage of DNA in the tail. In the second part of the study, the toxicity potential of AmxNPs on broilers was investigated by measuring biochemical parameters. In vivo results demonstrated that AmxNps did not cause a significant change in biochemical parameters, whereas Amx increased ALT, glucose, and cholesterol levels at certain sampling times. The obtained findings suggest that AmxNPs could be a safe promising potential drug in drug delivery systems.